Annual Records of Airborne Pollen of Poaceae in Five Areas in Lagos, Nigeria. Issue 4 (4th July 2018) - Adeniyi, Tiwalade Adeyemi; Adeonipekun, Peter Adegbenga; Olowokudejo, James Dele
Abstract: Poaceae pollen grains are known to be highly allergenic and they are potential causes of allergic respiratory diseases. In order to investigate the incidence of airborne Poaceae, and contribute to current trends in the development of aeropalynology/allergy studies in Nigeria, five highly populated locations in Central Lagos State, Surulere, Ebute-Metta, University of Lagos, Bariga and Gbagada, were sampled. Gravimetric aerosamples were collected monthly from January 2013 to December 2014. The lowest count in 2013 was recorded in the Ebute-Metta area (179), while the highest in 2013 was recorded in Gbagada (564). In 2014, the Surulere area (282) had the lowest count while Bariga (671) had the highest. The locations have similar monthly pollen distribution pattern but different peak months. Generally, Poaceae pollen counts were lowest in the months of June and July. These are therefore the safest months for Poaceae pollen hypersensitive individuals in the study areas. Relative humidity was the most important meteorological parameter with significant correlations in Ebute-Metta and Bariga locations. Results from this work will form the basis for a forecast service required to inform and educate the general public and allergy sufferers about Poaceae pollen distribution in Lagos State.